Speed fluctuation as a determinant factor of energy cost in Butterfly stroke - Barbosa, Tiago M. (2018)
The purpose of this study was to examine the relationships between the speed fluctuation of the centre of mass and the EC, in butterfly stroke. Five national level Portuguese swimmers performed one maximal and two sub-maximal (85% and 75%) 200-m butterfly swims in a 25-m swimming pool. Cardio-pulmonary and gas exchange parameters were measured breath by breath for each swim to analyze VO2 and other energetic parameters by portable metabolic cart (K4b2, Cosmed, Rome, Italy). A respiratory snorkel and valve system with low hydrodynamic resistance was used to measure pulmonary ventilation and to collect breathing air samples. Blood samples from the ear lobe were collected before and after each swim to analyze blood lactate concentration (YSI 1500L, Yellow Springs, US). Total energy expenditure (È-tot) and EC were calculated for each swim. The swims were videotaped (50 Hz) in sagital plane with a set of two cameras providing dual-media images from both underwater and above the water surface. The cameras were real time synchronised and the images were edited on a mixing table to create one single image of dual-media. APAS system (Ariel Dynamics Inc, USA) was used to analyse speed fluctuation for the centre of mass. Coefficients of variation for the horizontal velocity of the centre of mass along the stroke cycle (dV) were calculated. Linear regressions between the bioenergetic and biomechanical variables were computed, as well as, its 0.05). Coefficients of determination and correlation (p). There was a significant and linear relationship between È-tot and velocity (r=0.827, p=0.0005). Statistically significant correlation coefficient between the EC and the dV (r=0.807, p=0.0009) was found, the coefficient of determination being r2=0.651. This means that the increase in the EC being strongly associated with the increase in the speed fluctuation. The individual coefficients of correlation and determination between the EC and the dV were very high (mean r2 0.018, ranging from 0.973 to 1.000). The mean of individual correlation È= 0.986 0.009 coefficients was higher than the overall correlation coefficient (r=0.993 vs r=0.807) of the pooled data. It is concluded that the speed fluctuation of the centre of mass was related to less efficient swimming and vice versa in butterfly. We suggest that the swimmers should strive to improve their technique performances by avoiding large variations in the speed fluctuation.